Karakteristik Risiko Kesehatan Non Karsinogen Pada Remaja Siswa Akibat Pajanan Inhalasi Debu Particulate Matter <2,5 (PM2,5) - Rosalia, Ony; Wispriyono, Bambang; Kusnoputranto, Haryoto (Media Kesehatan Masyarakat Indonesia, 2018)
Increase in transport vehicles causes air pollution. Major pollutant of PM2.5 provides an enormous impact on health. Basin condition in Bandung causes the pollutants to be trapped because the pollutant cannot be released. The aim of this research is to analyze the health risks of junior high school students of SMPN 16 Bandung due to PM2.5 inhalation exposure in the school environment by using Environmental Health Risk Assessment method. PM2.5 concentration assessment was conducted at 10 points with a sample of 66 students’ grade VIII selected randomly. The average concentration of PM2.5, which was 29.34 μg/m3 was still below the standard value regulated by Government Regulation No. 41 of 1999 (65 μg/Nm3). The increased in real-time intake for 3 years and 12 years respectively were 7.53x10-5, 1.25x10-4, 5.02x10-4 mg/kg/day. PM2.5 intake was higher in students with light weight than students with heavy weight. Estimated health risks was expressed as risk quotient (RQ) calculated from the average of PM2.5 exposure intake on students and reference dose (RfC), RQ>1 indicated the risk needed to be controlled. The results of the analysis with the duration of real-time exposure for 3 years and 12 years showed a safe limit to PM2.5 exposure (RQ<1). Overall grade VIII students are not at risk of PM2.5 inhalation exposure in school environments.